Козацька педагогіка патріотизму про лицарський гарт української молоді - Лозко, Галина (Київський національний університет імені Тараса Шевченка, 2024)
Розглянуто основні ідеї козацької педагогіки, зокрема виховання патріотизму української молоді, гартування лицарських якостей особистості. Наголошено на шляхетних цінностях українського козацтва, любові до Батьківщини, вірності національним ідеалам, соціальній активності й готовності до самопожертви в ім’я рідної країни.

The relevance of the research. During the Russian-Ukrainian war, issues of national-patriotic education occupy a central place across all fields of the humanities: history, linguistics, literary studies, the arts, and Ukrainian studies as an integrative field of knowledge about one’s homeland. The deliberate erosion of the national component in education and its orientation toward liberal models and values has led to fragmentation of knowledge and perceptions among the younger generation about the true essence of Ukrainian history. The younger generation needs to comprehend the existential significance of their native land, language, and culture in the life of the nation and state. Ukrainian studies, with its concept of comprehensive knowledge about Ukraine, allow a transition to a new paradigm – a synergy of education and upbringing – rooted in a rich pedagogical heritage, including the tradition of knightly Cossack upbringing. This tradition, initiated in independent Ukraine, has yet to be fully utilized in educational and pedagogical processes. Patriotic upbringing has always been relevant and in demand. It has not yet fully tapped into the historically established tradition that prevailed in Ukraine from the princely and Cossack eras. This tradition remains a viable, authentically Ukrainian system of upbringing and knightly training for the youth. The purpose of the research. To draw the attention of Ukrainian scholars and educators to traditional Cossack pedagogy of patriotism as a nationally defined system of knightly upbringing for Ukrainian youth. It seeks to substantiate the importance of its study within Ukrainian studies and its implementation in the educational process during the Russian-Ukrainian war and in the post-war period. Conclusions. In the context of the Russian-Ukrainian war, patriotic education of Ukrainian youth acquires existential importance. It includes fostering a deep understanding among the younger generation of the value of their native land, language, and culture in the life of the nation and state. It also includes an awareness of Ukraine’s deep relations with the Kyivan Rus’ state and the Cossack experience of fostering Ukrainian knighthood, knightly training, and the ability to resist enemy aggression consciously and decisively – both in cultural and spiritual life and with weapons on the battlefield. The comprehensive discipline of Ukrainian studies offers such comprehensive educational opportunities.
Cossack Pedagogy of Patriotism about the Knightly Training of Ukrainian Youth
Keywords: козацька педагогіка; патріотизм; лицарський гарт; аристократизм духу; священний героїзм; манкуртизм; національний ідеал; Cossack pedagogy; patriotism; knightly training; aristocracy of spirit; sacred heroism; mankurtism; national ideal